-7m+3(m-6)=-6m-3(2-m)

Simple and best practice solution for -7m+3(m-6)=-6m-3(2-m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7m+3(m-6)=-6m-3(2-m) equation:


-7m+3(m-6)=-6m-3(2-m)

We simplify the equation to the form, which is simple to understand
-7m+3(m-6)=-6m-3(2-m)

Reorder the terms in parentheses
-7m+(+3m-18)=-6m-3*(2-m)

Remove unnecessary parentheses
-7m+3m-18=-6m-3+*(+2-m+)

Reorder the terms in parentheses
-7m+3m-18=-6m+(-6+3m)

Remove unnecessary parentheses
-7m+3m-18=-6m-6+3m

We move all terms containing m to the left and all other terms to the right.
-7m+3m+6m-3m=-6+18

We simplify left and right side of the equation.
-1m=+12

We divide both sides of the equation by -1 to get m.
m=-12

See similar equations:

| 121-25x^2= | | 7.2+4x+7=-32 | | 30-2(x-5)-8x=6(x-7)+24 | | 2x-2x-8=8 | | 2x+7x=-4(2+7x)+4(7+8x) | | (s+3)(3s^2-s+1)=0 | | 2x+6y=60 | | 8y+8x=9 | | x+(2x-5)=-2 | | 6*2+(12/6+3*2)-4*2 | | 2x^4+16x^2+-40=0 | | (8a^2)(2a^3-6)=0 | | 25x+10y=1250 | | 7=-7x+14/-7 | | 8(4q+5)-7q=20q-10 | | (5-y)(5+y)=0 | | P=5m+5w | | 2x^2-8=-40 | | 6/3-i | | 2a(a-4)(4a+2)=0 | | a=u*b*b | | (4/x-3)-1/x-3=4x/x^2-9 | | (5x-4)(5x-4)(5x-4)=0 | | 7z-7y=1 | | -7y+7x=1 | | (a-3)(a-1+4a^2)=0 | | Y=-x^2+50x+1800 | | (6x-7y)(7x-3y)=0 | | 2log^3(4X+6)-8=0 | | (8x+7y)(8x+7y)=0 | | (9w-4z)(9w+4z)=0 | | pir+2r+2h=44 |

Equations solver categories